Intertemporal Dimensions of International Economic Adjustment: Evidence from the Franco-Prussian War Indemnity - Gavin, Michael (American Economic Review, 2016)
Few topics in international economics have generated the intense and persistent interest that surrounds analysis of the transfer problem. In large part this reflects continuing fascination with the political and economic consequences of the victorious Allies' attempts to extract war reparations from Germany after the first World War. For economists, interest in this episode is surely increased by the clear analytical parallel between international transfer payments and other payments obligations, and in particular, international debt service (see e.g., Arminio Fraga, 1986). More generally, the economics of effecting an international transfer are immediately relevant for a broad range of questions in international economics, including in particular the economics of devaluation and, by extension, the economics of alternative exchange-rate regimes. Careful study of the macroeconomic consequences of episodes in which transfers were made would, therefore, provide important evidence on a much wider variety of issues than war reparations alone. The problem is that few such episodes exist. The World War I reparations are of little use here, because transfers were not in any real sense made from Germany to the Allies: rather the reverse. The lending booms studied by Frank W. Taussig, Jacob Viner, and others are of more use, but are suspect because the lending was clearly associated with a goods-market disturbance in the recipient countries. There is thus an element of endogeneity in these transfers which makes it unclear whether observed economic fluctuations during the period of transfer are due to the transfer itself or to the goods-market disturbance that induced the international flow of resources. This paper studies some aspects of one of the few major, economically exogenous international transfers in modern economic history: the war indemnity that followed the Franco-Prussian war of 1870-1871. This immense indemnity was demanded by, and from, an economy that was relatively unscathed by the war itself; and the transfer was actually paid. In this and other respects, the Franco-Prussian reparations seem to provide radically different economic and political lessons than those that have been drawn from the 1920's.1 The focus here is on some intertemporal dimensions of international transfers. These were somewhat neglected by the static theoretical discussions that eventually sorted out theoretical aspects of the Keynes-Ohlin debate, though contemporary analysis never lost sight of their importance (see e.g., James W. Angell, 1930).